What's new in atopic eczema? An analysis of systematic reviews published in 2010–11. (11th June 2013) - Torley, D.; Futamura, M.; Williams, H. C.; Thomas, K. S.
Summary This review provides a summary of key findings from 24 systematic reviews of atopic eczema (AE) published or indexed between 1 August 2010 and 31 December 2011, updating published summaries from previous years. Epidemiological evidence points to the protective effects of early daycare, endotoxin exposure, consumption of unpasteurized milk, and early exposure to dogs, but antibiotic use in early life may increase the risk for AE. With regard to prevention of AE, there is currently no strong evidence of benefit for exclusive breastfeeding, hydrolysed protein formulas, soy formulas, maternal antigen avoidance, omega‐3 or omega‐6 fatty‐acid supplementation, or use of prebiotics or probiotics. With respect to AE treatments, the most compelling new systematic review evidence was for proactive treatment with topical anti‐inflammatory agents (topical corticosteroids and topical calcineurin inhibitors) for the prevention of AE flares in patients with moderate to severe AE. A meta‐analysis of 4 trials confirmed the superiority of tacrolimus 0.1% over pimecrolimus for the treatment of AE, and a review of 17 trials found that tacrolimus (0.1% or 0.03%) was broadly similar in efficacy to mild/moderate topical corticosteroids. Evidence for the role of education in the management of AE was less conclusive, with evidence from randomized controlled trials showing mixed results. Further work is needed in this area to conduct high‐quality trials of educational interventions that are clearly described and reproducible. There is no clear evidence for the efficacy of homeopathy, botanical extracts or Chinese herbal medicine in the treatment of AE, as large well‐designed trials are lacking in these areas.